Emergence and evolution of mosaic penA-60 and penA-237 alleles in a Neisseria gonorrhoeae core genogroup that was historically susceptible to extended spectrum cephalosporins - Thomas IV, Jesse C.; Cartee, John C.; Hebrank, Katherine; St. Cyr, Sancta B.; Schlanger, Karen; Raphael, Brian H.; Kersh, Ellen N.; Joseph, Sandeep J. (Frontiers in Microbiology, 2024)
Introduction: Neisseria gonorrhoeae (Ng) has successively developed resistance to all previously recommended antimicrobial therapies, with ceftriaxone being the last option for monotherapy of gonorrhea. Global emergence and international spread of the FC428 clone derived mosaic penA-60 allele, associated with highlevel ceftriaxone minimum inhibitory concentrations (MICs) in non FC428 clone Ng lineages, has become an increasing concern. The penA-60 allele carrying Ng was first identified in the U.S. in Las Vegas, Nevada (2019; GCWGS-102723), with a multi-locus sequence type (MLST)-1901 strain, in a non FC428 clone Ng lineage, which is associated with a historically ceftriaxone susceptible core genogroup. Later in 2022, an allele genetically similar to penA-60, mosaic penA-237, was identified in the UK (H22-722) and France (F92) with high-level ceftriaxone MICs and both belonged to MLST-1901. Methods: In this study, we assessed phylogenomic relatedness and antimicrobial resistance (AMR) determinant profiles of these three isolates with high-level ceftriaxone MICs among a global collection of 2,104 genomes belonging to the MLST-1901 core genome cluster group 31, which includes strains separated by a locus threshold of 200 or fewer differences (Ng_cgc_200). Recombination events in and around the penA coding region were catalogued and potential sources of inter species recombinant DNA were also inferred.The global population structure of MLST-1901 core genogroup falls into 4 major lineages. Isolates GCWGS-10723, F92, and H22-722 clustered within Lineage 1, which was dominated by non-mosaic penA-5 alleles. These three isolates formed a clade within Lineage 1 that consisted of isolates from North America and southeast Asia. Neisseria subflava and Neisseria sicca were identified as likely progenitors of two independent recombination events that may have led to the generation of mosaic penA-60 and penA-237, within a possible non-mosaic penA-5 background.Discussions: Our study suggests that there are multiple evolutionary pathways that could generate concerning mosaic penA alleles via homologous recombination of historically susceptible Ng lineages with Neisseria commensals. Enhanced surveillance of gonococcal strains and Neisseria commensals is crucial for understanding of the evolution of AMR, particularly in less-studied regions (e.g., Asia), where high-level ceftriaxone MICs and multi-drug resistance are more prevalent.